Narracyjność językowego obrazu ludzkiej egzystencji w polskich i rosyjskich połączeniach wyrazowych zawierających czasowniki ruchu iść/идти, сhodzić/ходить (na materiale leksykograficznym) - Zając-Haduch, Karina (Studia Rossica Posnaniensia, 2021)
The purpose of the study is to show narrative (narration) as a category that combines individual elements of knowledge, expressed through language, and, thus, ensures the cohesion of the linguistic and cultural picture of the world. In the light of this concept, the linguistic-cultural picture of the world is understood as a dynamic, multi-layered narrative depending on the accepted points of view, intentions, approaches and methods of conceptualization, categorization and axiologization of reality adopted in this culture. This article deals with the narrative of human life, which creates the expressions in Polish and Russian that contain verbs of movement. The analysis of the chosen phrases allows us to determine how similar life experiences are perceived in both languages, as well as to what extent the cultural conditions and the genetic proximity of both languages have an influence on similarities in the image of human existence.